2015
DOI: 10.1111/1440-1681.12390
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CYP2C19 alleles, pharmacokinetic and pharmacodynamic variation of clopidogrel and prasugrel in Bangladeshi population

Abstract: The extent to which cytochrome P450 (CYP) 2C19 genotype influences the effectiveness of clopidogrel remains uncertain due to considerable heterogeneity between studies. We used the polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) method for genotyping loss of function (LOF) allele, CYP2C19*2 and gain of function (GOF) allele, CYP2C19*17 in 163 patients undergoing PCI and 165 healthy volunteers from an ethnically distinctive Bangladeshi population. Thirty-eight patients took prasugr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Many studies showed that CYP genetic variants had a significant influence on the pharmacokinetic and pharmacodynamic responses to clopidogrel, causing diminished antiplatelet response [24]. However, prasugrel is believed to be less affected by genotypic variability [25][26][27]. Moreover, one study found no significant difference in pharmacodynamic response for prasugrel 5 or 10 mg [28], what is in disagreement with the index data.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies showed that CYP genetic variants had a significant influence on the pharmacokinetic and pharmacodynamic responses to clopidogrel, causing diminished antiplatelet response [24]. However, prasugrel is believed to be less affected by genotypic variability [25][26][27]. Moreover, one study found no significant difference in pharmacodynamic response for prasugrel 5 or 10 mg [28], what is in disagreement with the index data.…”
Section: Discussionmentioning
confidence: 97%
“…3 ml of venous blood was collected from all patients in sterile tubes containing EDTA-Na 2 and stored at -80 C until genomic DNA (gDNA) extraction. gDNA was isolated from blood by previously published method [20]. The quantity and purity of the isolated DNA were assessed by using a UV Spectrophotometer (UV Prove v2.1) at 260 nm.…”
Section: Genotypingmentioning
confidence: 99%
“…Substantial clinical trials that evaluated higher loading and maintenance dose of clopidogrel in ACS/PCI patients have resolved that adjusting the dose does not downgrade the incidence of death [35]. Prasugrel and ticagrelor, on the other hand, were superior to clopidogrel in a large-scale randomized trial of ACS patients with planned PCI which showed 42% and 26 % reduction in-stent thrombosis, respectively [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, these may not replace clopidogrel for all kinds of patients due to contraindication in some patients [36], insufficient long-term toxicity data [37] and also lack of statistically significant data [38].…”
Section: Introductionmentioning
confidence: 99%